Stability, elasticity and electronic structures of Co-Zr binary intermetallic compounds. Issue 7 (2nd April 2020) - Li, K.R.; Lu, W. F.; Li, C.J.; Şopu, D.; Sarac, B.; Yi, J.H.; Tan, J.; Gao, P.; Eckert, J.
ABSTRACT: The structural properties, enthalpies of formation and entropic temperatures of five stable Co-Zr intermetallics were systematically investigated by first-principles calculations. The calculated enthalpy of formation was used to measure the phase stability of the Co-Zr intermetallic compounds, and the results reveal that CoZr has the highest phase stability among these Co-Zr compounds. Considering the change of temperature, the entropic temperature TS was used to illustrate the high-temperature stability of the Co-Zr intermetallic compounds. Additionally, the elastic constants, anisotropy indexes and Debye temperatures have been calculated. According to the calculated anisotropy indexes, CoZr2 has the highest elastic anisotropy among the Co-Zr binary compounds. Furthermore, the bonding characteristics of these compounds have also been investigated by calculating the electronic structures.